Recombinant human thrombopoietin improves the efficacy of intermediate-dose cyclophosphamide plus granulocyte colony-stimulating factor in mobilizing peripheral blood stem cells in patients with multiple myeloma: A cohort study. Issue 50 (December 2017) - Wang, Guorong; Chen, Wenming; Wu, Yin; Li, Yanchen; Leng, Yun; Liu, Aijun
Abstract : Abstract: The combination of intermediate-dose cyclophosphamide (ID-CTX) and granulocyte colony-stimulating factor (G-CSF) fails to mobilize peripheral blood stem cells (PBSCs) in approximately 20% of treated patients with multiple myeloma (MM). In this cohort study, patients with MM underwent PBSC mobilization with either an ID-CTX plus G-CSF plus recombinant human thrombopoietin (rhTPO) regimen (72 patients; TPO group), or an ID-CTX plus G-CSF regimen (70 patients; non-TPO group). In the TPO group, the median CD34+ harvest was 5.36 × 10 6 per kg of body weight (0.50–22.39 × 10 6 per kg of body weight), with a harvest success rate of 91.7% (66/72), and an excellence rate of 55.6% (40/72). In the non-TPO group, the median CD34+ harvest was 3.30 × 10 6 per kg of body weight (0.20–21.14 × 10 6 per kg of body weight), with a harvest success rate of 75.7% (53/70), and an excellence rate of 25.7% (18/70). The median count of the CD34+ cells collected, success rate of collection, and excellence rate of collection were significantly higher in the TPO group than in the non-TPO group ( P =.0001, P =.01, and P = .0001, respectively). Time to granulocyte and platelet engraftment was faster among patients in the TPO group than that in those from the non-TPO group. No platelet engraftment delay (>21 days) was observed among patients in the TPO group, while 3 patients in the non-TPO group displayed delayed platelet engraftment. Adding rhTPO to the ID-CTX chemotherapy plus G-CSF regimen improved treatment efficacy in mobilizing PBSCs for autologous hematopoietic stem cell transplantation.